Impacts of land use on water infiltration in various soils of the Cantareira System - Robert, Evens (2021)
The groundwater recharge depends on deep drainage. For this to occur, initially there must be infiltration of water into the soil. The soil use and management strong influence the process of water infiltration. In Cantareira System, the knowledge of soil classes combined with the land use is an essential for indicate the best use of the soil for each soil class, in order to promote an improvement in water recharge. The aim of this research was to determine the soil physical-hydric properties and the rate of basic infiltration in four different land uses under three soil classes. This research was carried out considering land uses of native forest, eucalyptus, rotated grazing and continuous grazing which occur in Red Yellow Argisols, Haplic Cambisols, and Regolith Neosols in the Cantareira System. Soil physical properties determined in laboratory were texture, bulk density, micro and macro porosity, total porosity, and soil aggregates. Soil infiltration was determined by using a double ring infiltrometer and Horton model was performed to achieve the soil infiltration rate. The results were subjected to analysis of variance (ANOVA) and the means by Tukey's test (5% probability), and principal component analysis (PCA) was performed in the RStudio software. Cambisols revealed as having the highest infiltration rate under the use of native forest compared to other soils. For Neosols, the infiltration rate is almost the same, regardless of land uses. For Argisols, the rate of basic infiltration is higher under Eucalyptus compared to other uses. The native forest in Cambisols and neosols showed a higher rate of water infiltration compared to argisols and being an important area for preservation, strongly influencing the water recharge into the soil. Animal trampling may have caused compaction in continuous grazing, reflecting very low water infiltration values in the soils analyzed.